HLA class II susceptibility pattern for type 1 diabetes (T1D) in an Iranian population. (18th June 2015) - Kiani, J.; Hajilooi, M.; Furst, D.; Rezaei, H.; Shahryari‐Hesami, S.; Kowsarifard, S.; Zamani, A.; Solgi, G.
Summary This study aimed to determine the HLA‐DRB1/HLA‐DQB1 susceptibility and protection pattern for type 1 diabetes (T1D) in a population from Hamadan, north‐west of Iran. A total of 133 patients with T1D were tested for HLA‐DRB1 and HLA‐DQB1 alleles using PCR‐SSP compared to 100 ethnic‐matched healthy controls. Alleles and haplotypes frequencies were compared between both groups. The most susceptible alleles for disease were HLA‐DRB1*03:01, DRB1*04:02, DQB1*02:01 and DQB1*03:02, and protective alleles were HLA‐DRB1*07:01, *11:01, *13:01, *14:01 and DRB1*15 and HLA‐DQB1*06:01, *06:02 and *06:03. Haplotype analysis revealed that patients with T1D had higher frequencies of DRB1*03:01–DQB1*02:01 (OR = 4.86, P < 10−7) and DRB1*04:02–DQB1*03:02 (OR = 9.93, P < 10−7) and lower frequencies of DRB1*07:01–DQB1*02:01 (P = 0.0005), DRB1*11:01–DQB1*03:01 (P = 0.001), DRB1*13:01–DQB1*06:03 (P = 0.002) and DRB1*15–DQB1*06:01 (P = 0.001) haplotypes compared to healthy controls. Heterozygote combination of both susceptible haplotypes (DR3/DR4) confers the highest risk for T1D (RR = 18.80, P = 4 × 10−5). Additionally, patients with homozygote diplotype, DR3/DR3 and DR4/DR4, showed a similar risk with less extent to heterozygote combination (P = 0.0004 and P = 0.01, respectively). Our findings not only confirm earlier reports from Iranians but also are in line with Caucasians and partly with Asians and some African patients with T1D. Remarkable differences were the identification of DRB1*04:01–DQB1*03:02, DRB1*07:01–DQB1*03:03 and DRB1*16–DQB1*05:02 as neutral and DRB1*13:01–DQB1*06:03 as the most protective haplotypes in this study.